Influence of Chemical Composition of Lifting Equipment Material On Their Performance - G. Amosov, Alexey; K. Rozhdestvensky, Oleg (International Journal of Integrated Engineering, 2023)
The presented study refers to the use of load-handling chain slings. The theoretical calculation shows the high reliability and virtually trouble-free operation of a metal welded circuit, but the study conducted by the authors suggests otherwise, the use of chain hangers can adversely affect the manufacturing and testing stage without proper input control of the chemical composition of the material used. The introduction describes the relevance of the work and a brief historical background of the existence of this problem, as well as the terms used in the work. The next part presents a methodology for calculating the load and reliability; the quantitative values of reliability indicators, methods for obtaining them and a methodology for calculating reliability by the criterion of strength are shown. The scheme of operation of the emission spectrometer and the technology of its application are presented. In the conclusions, there are practical recommendations and coincidence of the results of the study with known facts from the materials sciences